PENERAPAN DINDING INTERAKTIF PADA SARANA EDUKASI BAGI KOMUNITAS ANAK JALANAN - Sella Serina; Sutrisnowati Machdijar (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
The number of street children continues to increase due to the tendency of children who are easily influenced to become street children due to their surroundings. Street children are in a vulnerable phase and are easily influenced by their environment to become street children, so some of them have to drop out of school because the majority prefer to help their parents make a living. This causes street children to grow up with educational values instilled from an early age so they have a lack of interest in learning. The educational needs of street children require learning methods that are appropriate to their behavior and activities. The majority of street children's activities are in the form of working to earn money, causing them to be less able to channel their hobbies and express themselves. Activities to channel their hobbies, talents and interests related to the arts and sports by forming a community. The research method used is in the form of a third place as a community builder and behavioral architecture to determine learning adapted to the nature, character and behavior of street children. The learning method is in the form of learning while playing with learning phases based on the level of focus of children's learning through interactive and adaptive learning media with interactive wall media. Types of interactive learning include academic in the form of learning to read, count, and color; non-academic in the form of arts and skills, and physical activities to train children's sensory and motor development. The application of interactive walls through the use of materials and spatial concepts that are flexible so that they can change functions according to needs and form concepts that describe the character of street children. Keywords:  Behaviour Architecture; Community; Education; Interactive Wall; Street Children Abstrak Jumlah anak jalanan terus meningkat akibat kecenderungan anak yang mudah terpengaruh menjadi anak jalanan akibat lingkungan sekitarnya. Anak jalanan berada di fase yang rentan dan mudah terpengaruh oleh lingkungannya untuk menjadi anak jalanan sehingga beberapa di antaranya harus putus sekolah karena mayoritas lebih memilih membantu orang tuanya mencari nafkah. Hal ini menyebabkan anak jalanan tumbuh dengan nilai pendidikan yang tertanam sejak dini sehingga memiliki kurangnya minat dalam belajar. Kebutuhan pendidikan anak jalanan ini membutuhkan metode pembelajaran yang sesuai dengan perilaku dan aktivitasnya. Mayoritas aktivitas anak jalanan berupa bekerja untuk mencari uang sehingga menyebabkan mereka kurang dapat menyalurkan hobi dan mengekspresikan diri mereka. Kegiatan untuk menyalurkan hobi, bakat, dan minatnya terkait bidang seni dan olahraga dengan suntuk membentuk komunitas. Metode penelitian yang digunakan berupa tempat ketiga sebagai pembentuk komunitas serta arsitektur perilaku untuk menentukan pembelajaran disesuaikan dengan sifat, karakter, serta perilaku anak jalanan. Metode pembelajaran berupa belajar sambil bermain dengan fase pembelajaran berdasarkan tingkat fokus belajar anak melalui sarana pembelajaran yang interaktif dan adaptif dengan media dinding interaktif. Jenis pembelajaran interaktif meliputi akademik berupa belajar membaca, berhitung, dan mewarnai; non akademik berupa seni dan keterampilan, dan aktivitas fisik untuk melatih perkembangan sensorik dan motorik anak. Penerapan dinding interaktif melalui penggunaan material  serta konsep ruang yang bersifat fleksibel sehingga dapat berubah fungsi sesuai kebutuhan serta konsep bentuk yang menggambarkan karakter anak jalanan.